Electrospraying as a Technique for the Controlled Synthesis of Biocompatible PLGA@Ag2S and PLGA@Ag2S@SPION Nanocarriers with Drug Release Capability - Alexis Alvear-Jiménez; Irene Zabala Gutierrez; Yingli Shen; Gonzalo Villaverde; Laura Lozano-Chamizo; Pablo Guardia; Miguel Tinoco; Beatriz Garcia-Pinel; José Prados; Consolación Melguizo; Manuel López-Romero; Daniel Jaque; et al. (MDPI AG, 2022)
Ag2S nanoparticles are near-infrared (NIR) probes providing emission in a specific spectral range (~1200 nm), and superparamagnetic iron oxide nanoparticles (SPION) are colloidal systems able to respond to an external magnetic field. A disadvantage of Ag2S NPs is the attenuated luminescent properties are reduced in aqueous media and human fluids. Concerning SPION, the main drawback is the generation of undesirable clusters that reduce particle stability. Here, we fabricate biocompatible hybrid nanosystems combining Ag2S NPs and SPION by the electrospraying technique for drug delivery purposes. These nanostructures are composed of poly(lactic-co-glycolic acid) (PLGA) as the polymeric matrix in connection with both Ag2S NPs and SPIONs. Initially, we fabricate a hybrid colloidal nanosystem composed of Ag2S NPs in connection with PLGA (PLGA@Ag2S) by three different routes, showing good photoluminescent (PL) properties with relatively high average decay times. Then, we incorporate SPIONs, obtaining a PLGA polymeric matrix containing both Ag2S NPs and SPION (PLGA@Ag2S@SPION). Interestingly, in this hybrid system, the location of Ag2S NPs and SPIONs depends on the synthesis route performed during electrospraying. After a detailed characterization, we demonstrate the encapsulation and release capabilities, obtaining the kinetic release using a model chemotherapeutic drug (maslinic acid). Finally, we perform in vitro cytotoxicity assays using drug-loaded hybrid systems against several tumor cell lines.